A Descriptive Analysis of Public Understanding and Attitudes of Renewable Energy Resources towards Energy Access and Development in Nigeria - Akinwale, Yusuf Opeyemi; Ogundari, Ibikunle Olalekan; Ilevbare, Oluwatosin Eniola; Adepoju, Adeyemi Oluwaseun (International Journal of Energy Economics and Policy, 2014)
Nigeria government has set a target of becoming among the top 20 economies by the year 2020. The argument here is not whether this can be achieved or not within the stipulated time, but rather achieving a sustainable economic growth through a clean energy system. The development of renewable energies in every region of the country is one of the tactics that can be used to achieve clean energy. This paper examined the attitudes and understanding of the public towards renewable energy sources and technologies so as to enhance the provision of electricity. The study was conducted in the south west Nigeria using a field questionnaire survey. The study found out that the large numbers of respondents are aware of renewable energy but they do not have a deep understanding of it. Most of the respondents support the use of renewable energy to supplement the current national grid instead of the present dominance of diesel/petrol generating set. Also, the public are willing to pay more for electricity supply once it is stable. Meanwhile, the willingness to pay more for the electricity decreases with the respondents’ age but increases with the respondents’ income. This implies that people will be willing to pay more for electricity when their incomes increase and also when they are relatively young. The study therefore suggests strong political commitment of Nigeria government on renewable energy applications as well as creation of enabling environment for the private sectors to successfully utilised renewable energy technologies. Keywords: renewable energy sources, Technologies; public attitudes and understanding JEL Classifications: D11; Q28; R11